(untitled) (International Journal of Engineering and Computer Science, 2013)
In todays modern world, social networking has became an inseparable part of human life. Indeed, social networking has been the story of this decade. NFC is a complementary technology that facilitates social networking in a secure way. Social networking is evolving beyond just interactions between individuals to include commercial nodes. A business can be enhanced or can even thrive solely through social networks. The popularity of social networking as a de facto medium of communication among the thinking public is dampened only by privacy and security concerns. In this paper we will discuss how NFC technology helps in social networking and bring people closer and also the advent of mobile devices (and their embracing of NFC technology) in social networking. By using NFC technology, social networking is no longer restricted to the PC only.